Traditional Kolam challenges in the Indian community in the Klang Valley, Malaysia - Murugan, Ilangeswary (2022)
Indian folk art, which reflects their artistic ability, is closely related to sculptures, pottery, cloth weaving, wood carving, and Kolam. Kolam is a type of folk art practised by Indians in Malaysia that reveals their cultural identity and aesthetic values. This floor drawing, which is a part of Indian traditions, is an important part of Indian cultural heritage. Kolam designs represent symbols of happiness, good fortune, wealth, and happiness, and are primarily performed by Indian women. The purpose of this research is to uncover the different types of Kolams, the challenges that its practitioners face, and ways to improve Kolam practise. The study focused on the Indian community in Malaysia’s Klang Valley. Data was gathered using a purposive sampling technique, and an online questionnaire was made available for three weeks. Only 410 of the 416 questionnaires received were analysed, with the rest being invalid. According to the findings of this study, respondents were aware of the various types of Kolams that were commonly used in the community. Despite the small sample size, the results provide insight into the various challenges faced by practitioners in preserving the drawing of Kolam. There were numerous suggestions made to improve Kolam practise among community members. Traditional Kolam practise has been influenced by changes in Indian culture. If efforts are not made to preserve this form of traditional practise, it may be gradually eroded by the everincreasing influences of globalisation and urbanisation. As a result, these challenges must be taken seriously, and every effort must be made to keep this art form alive as a cultural heritage for future generations.